EXPLOITATION IN ONLINE CONTENT MODERATION - Frost-Arnold, Karen (AoIR Selected Papers of Internet Research, 2023)
This paper presents a normative framework for evaluating the moral and epistemic exploitation that online content moderation workers experience while working for social media companies (often as subcontractors or as Mechanical Turk workers). I argue that the current labor model of commercial content moderation (CCM) is exploitative in ways that inflict profound moral harm and epistemic injustices on the workers. This detailed account of exploitation enables us to see more clearly the contours and causes of the moral and epistemic injustice involved in CCM, and helps us understand precisely why these forms of exploitation are unjust. It also suggests some practical solutions for a more just labor model for the moderation work that shapes our online ecosystem.